Characterization and qualification of a CRNA eye dosimeter - Larabi-Harfouche, K.; Dari, F.; Herrati, A.; Medkour-Boushaki, G.; Lounis-Mokrani, Z. (Perspectives in science, 2019)
The aim of this work is to study the calibration methodology of a new eye dosimeter, developed by Dosimetry Laboratory of the Nuclear Research Center of Algiers, using TLD-700 thermoluminescent detectors (LiF: Mg, Ti). Qualification and type test of this dosimeter have been performed in terms of operational quantity Hp(3) at Secondary Standard Dosimetry Laboratory (SSDL) using the cylindrical phantom according to ISO 12794, ORAMED 2012 and IEC 62387, 2012. Furthermore, two dosimeter holders have been tested for two positions (frontal and lateral) in order to determine the “best dosimeter position” which allows good estimation of dose received by lens.